2021
DOI: 10.1126/science.abe1916
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti–SARS-CoV-2 IgG antibodies in Kenyan blood donors

Abstract: The spread of SARS-CoV-2 in Africa is poorly described. The first case of SARS-CoV-2 in Kenya was reported on March 12, 2020 and an overwhelming number of cases and deaths were expected but by July 31, 2020 there were only 20,636 cases and 341 deaths. However, the extent of SARS-CoV-2 exposure in the community remains unknown. We determined the prevalence of anti–SARS-CoV-2 IgG among blood donors in Kenya in April-June 2020. Crude seroprevalence was 5.6% (174/3098). Population-weighted, test-performance-adjust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
214
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(233 citation statements)
references
References 29 publications
14
214
4
1
Order By: Relevance
“…A Spanish seroprevalence survey found an overall seroprevalence of only 4.7%-5% in May of 2020, which increased to 14.4% in the more densely populated central provinces [9]. A recent survey of 3098 Kenyan blood donors found an overall seroprevalence of 5.6% (population-weighted seroprevalence 4.3%), which was highest in those living in the three largest urban counties of Mombasa PLOS ONE (8.0%), Nairobi (7.3%) and Kisumu (5.5%) [28]. Similar to our study, their results suggested that infection in Kenya was more widespread than the current PCR-based testing strategies would suggest.…”
Section: Discussionmentioning
confidence: 99%
“…A Spanish seroprevalence survey found an overall seroprevalence of only 4.7%-5% in May of 2020, which increased to 14.4% in the more densely populated central provinces [9]. A recent survey of 3098 Kenyan blood donors found an overall seroprevalence of 5.6% (population-weighted seroprevalence 4.3%), which was highest in those living in the three largest urban counties of Mombasa PLOS ONE (8.0%), Nairobi (7.3%) and Kisumu (5.5%) [28]. Similar to our study, their results suggested that infection in Kenya was more widespread than the current PCR-based testing strategies would suggest.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of parturient women (6.2%, 80/1,293) in Philadelphia possessed IgG and/or IgM SARS-CoV-2-specific antibodies (Flannery et al, 2020). It was also reported that 5.6% (174/ 3,098) of blood donors had anti-SARS-CoV-2 IgG (Uyoga et al, 2020). The prevalence of SARS-CoV-2 antibodies in populations was clearly related to local epidemic levels.…”
Section: Humoral Responses To Sars-cov-2 Infection In Asymptomatic Pomentioning
confidence: 97%
“…33 Without any other rational explanations, the results support our hypothesis that immunity to type S virus underlies the exacerbation of COVID-19 in Europe. 5 Serosurveys in Kenya have suggested that the epidemic in Africa was like that in the West; 34 however, in contrast to the West, most patients were asymptomatic or mildly ill. On the African continent, in contrast to Europe, many of the epidemics were due to Clade S. Our previous analysis suggested that the outbreak of type K virus after type S offsets the effect of type S to increase CFR. T14I mutation is also present in peptides predicted as HLA Class I T cell epitopes.…”
Section: Discussionmentioning
confidence: 99%